THE RELATIONSHIP BETWEEN DENTAL CARIES STATUS AND QUALITY OF LIFE IN STUDENTS OF MUHAMMADIYAH 3 SEMARANG HIGH SCHOOL - Syalsya Billa Dinda Safira; Tri Nurhidayati; Hayyu Failasufa (FKG ULM, 2025)
Background : Dental caries is a prevalent oral health issue among adolescents, affecting not only their oral health but also their overall quality of life. Investigating the relationship between dental caries and quality of life is crucial because dental caries can impact various aspects of adolescents' lives, including nutrition, sleep, aesthetics, and education, thereby highlighting the need for comprehensive understanding and intervention strategies to improve adolescent health outcomes. Method: This analytical observational study utilized a cross-sectional design involving 337 students from SMP Muhammadiyah 3 Semarang, with a sample of 183 selected through stratified random sampling. Inclusion criteria included students aged 12-14 years who provided informed consent, while exclusion criteria involved those absent or incomplete in the questionnaire. Ethical clearance was obtained, and data collection occurred on February 21, 2024, using the DMFT index for dental caries and a validated quality of life questionnaire. Data analysis included the Kolmogorov-Smirnov test for normality and the Spearman Rank test to assess relationships between variables. Result : There is a statistically significant relationship between dental caries status and quality of life in students with p value of 0.014 (<0.05). Conclusion : The findings of this study indicate a significant relationship between dental caries and the quality of life among adolescents aged 12-14 years. Addressing dental caries is essential for improving overall well-being and quality of life in this population. Keywords: adolescents health, CPQ11-14, dental caries, quality of life